PENGARUH MODERNITAS SIKAP KEWIRAUSAHAAN TERHADAP KEBERHASILAN UMKM TEMPE DAN TAHU DI KABUPATEN BOGOR - Andina Dyah Rahmadhani Aditya; Heny Kuswanti Suwarsinah Daryanto (Forum Agribisnis, 2015)
Entrepreneurship widely-known as the boosting factor for competent human resources. Entrepreneurship has relation with the development of SMEs, such as business in tempeh and tofu. Bogor has many soybean products SMEs. The entrepreneurs must have modernity entrepreneurship attitude to develop the business. The purpose of this study is to analyze the influence of modernity entrepreneurship attitude towards the success of soybean SMEs unit in Bogor Regency. The data were analyzed descriptively and quantitatively using Partial Least Square analyzing the influences between latent variables. The results showed that the attributes of modernity entrepreneurship attitude that are found for tempe producers are innovative, hardwork, respect for time, and individual responsibility, where attributes for the entrepreneurs who produce tofu are innovative, hardwork, respect for time, achievement motivation, self-confidence, and individual responsibility. Attributes of success of the business run by both tempe and tofu producers are the increasing number of consumer and profit gained. Modernity entrepreneurship attitude significantly influenced the success of the business. Government’s support are required in order to support the capital incentive, events of entrepreneurship competition, and achievement/reward for the entrepreneurs.